Distribusi dan Situasi Vaksinasi COVID-19 - Letifa Rahmadani; rasmi zakiah oktarlina; agustyas tjiptaningrum (Medula, 2023)
Developing a safe and effective COVID-19 vaccine and getting it into people's hands is a global priority that can bring hope for ending the COVID-19 pandemic. However, the application of this vaccine can differ between countries. This study takes a close look at vaccination policies, vaccination plans, and their implementation in Indonesia which may be relevant to other developing countries. Supply constraints are one of the problems faced by developing countries, including Indonesia, especially at the beginning of the vaccination period due to relatively low coverage of vaccination plans. Limited supply from producers is one of the biggest challenges in the initial vaccination period. The plan to procure early vaccinations in Indonesia will allow Indonesia to obtain more vaccine supplies over time to cover sufficient populations to acquire immunity. Apart from the importance of vaccination distribution, the willingness of individuals to receive the COVID-19 vaccine is a major challenge in many countries. However, the demand for a COVID-19 vaccine is relatively high among the world's general population. However, skepticism is a major obstacle to efforts to control the current pandemic. To promote the equitable distribution of vaccines, it is necessary to ensure that levels of price, access and acceptance are independent of available resources among individuals and countries. This can be achieved by raising awareness about the health-protective impact of vaccines among all citizens. The issue of vaccine distribution has become critical and a significant challenge in dealing with COVID-19, a global epidemic that has turned into a national disaster. Therefore, this must be addressed immediately because it can directly increase cases of COVID-19. This literature review discusses the distribution of vaccines and the problems encountered during the process.